The Melbourne Mastoidectomy Scale: Validation of an end‐product dissection scale for cortical mastoidectomy. (25th May 2020) - Talks, Benjamin James; Lamtara, Jesslyn; Wijewickrema, Sudanthi; Gerard, Jean‐Marc; Mitchell‐Innes, Alistair Macleold; O'Leary, Stephen
Abstract: Introduction: Cortical mastoidectomy is a common otolaryngology procedure and represents a compulsory part of otolaryngology training. As such, a specific validated assessment score is needed for the progression of competency‐based training in this procedure. Although multiple temporal bone dissection scales have been developed, they have all been validated for advanced temporal bone dissection including posterior tympanotomy, rather than the task of cortical mastoidectomy. Methods: The Melbourne Mastoidectomy Scale, a 20‐item end‐product dissection scale to assess cortical mastoidectomy, was developed. The scale was validated using dissections by 30 participants (10 novice, 10 intermediate and 10 expert) on a virtual reality temporal bone simulator. All dissections were assessed independently by three blinded graders. Additionally, all procedures were graded with an abbreviated Welling Scale by one grader. Results: There was high inter‐rater reliability between the three graders ( r = .9210, P < .0001). There was a significant difference in scores between the three groups ( P < .0001). Additionally, there was a large effect size between all three groups: the differences between the novice group and both the intermediate group ( P = .0119, η 2 = 0.2482) and expert group ( P < .001, η 2 = 0.6356) were significant. The difference between the intermediate group and expert group again had a large effect size ( η 2 = 0.3217), but was not significant. The Melbourne Mastoidectomy Scale correlated well with an abbreviated Welling Scale ( r = .8485, P < .0001). Conclusion: The Melbourne Mastoidectomy Scale offers a validated score for use in the assessment of cortical mastoidectomy.